PPP booking room web application for Unit KO UiTM KJM / Nursalsabila Saruni - Saruni, Nursalsabila (2021)
The Co-curricular Unit (Unit KO) is one of the organizations that operates and functions under of Student Affairs Division (Bahagian Hal Ehwal Pelajar - BHEP) and their office is located at Pusat Persatuan Pelajar (PPP) UiTM KJM. Co-curricular Unit is the one that manages and accepts any booking request among ten rooms or locations in the PPP. The problems occur when the Unit KO itself finds that it is tedious for them as well as the student or lecturer to practice the current manual process of booking. Besides, the Unit KO could not offer a flexible booking that the booking must be made during weekdays within office hours only. The Unit KO also finds that to notify people who made a booking request via call is not effective that it is needed for the Unit KO to go for few tries to call the respective club or association as they cannot be reached easily. Hence, this project is aimed to help the Unit KO in managing their booking services with the existence of a web application. The Waterfall Methodology is employed using the first three phase starts with the knowledge gathering and analysis, followed by the design phase and the implementation phase. Based on the outcomes of findings, this system allows students or lecturers from any club or association in UiTM KJM to book any available room added by the Unit KO itself. The admin of the web application might trigger the system to send a booking confirmation email to the respected user of the system. All the booking list and others booking slot can be referred from the booking calendar that exist within the system. It will show some important details such as room name, booking duration as well as the name of club or association involved. As the system has its limit that users could not have any room’s pictures for reference, it is highlighted for the future work in which the next developer might consider improving the system’s features for a better users’ experience.